Assessment Of Knowledge, Attitude And Practice (kap) Correlation Among Cfs Iium Students Towards Sustainable Development Goals (sdgs) - Norfazlina Mohd Sahaharuddin; Nor Nazihah Chuweni; Azyril Iskandar Abdullah; Noor Azura Mat Said; Kamaril Azlah Teruk; Nazira Zubir (ASIAN SCHOLARS NETWORK, 2025)
Indexed Publication (Tier 3)